Child and Adolescent Psychosocial Care Center service use profile in Brazil: 2008 to 2012 (2019)
ABSTRACT: Objective: To describe the service use profile of Child and Adolescent Psychosocial Care Centers (Centro de Atenção Psicossocial Infanto-Juvenil [CAPSi]) in Brazil regarding diagnostic categories, sociodemographic aspects, and care modalities between 2008 and 2012. Methods: A descriptive, ecological study was performed using data from the Unified Health System regarding high-complexity procedure authorizations (Autorização de Procedimentos de Alta Complexidade [APAC]) for the period from 2008-2012. The variables sex, age, diagnosis (F00-F99 of ICD-10), and type of care provided were examined. The data were processed using TabWin and STATA version 12. Results: A total of 837,068 records were examined, each representing one visit to CAPSi. Most visits were by male users (68.8%). The most common diagnoses were hyperkinetic disorders (13%), pervasive developmental disorders (12.4%), and conduct disorders (8.4%). Conclusions: Behavioral and emotional disorders that usually appear during childhood or adolescence and psychological development disorders were frequent, with more than 50% of the latter comprising autism spectrum disorders. Regional differences were observed, with a higher presence of this diagnosis in the Southeast, while the North and Northeast had a high percentage of visits due to mental retardation.